URGENSI MANAJEMEN ZAKAT DAN WAKAF BAGI PENINGKATAN KESEJAHTERAAN MASYARAKAT - Aini, Quratul (ZISWAF, 2014)
Zakat and Waqf is a religious dimension which has godlike and socialdimensions, so zakat and waqf is one that can be used for the welfare of society. And to achieve that goal is very necessary to have a management  zakat and waqf professional and accountable.